Synthesis of Near‐Infrared‐Emitting Benzorhodamines and Their Applications to Bioimaging and Photothermal Therapy. Issue 50 (17th August 2020) - Dai, Mingchong; Lee, Hyori; Yang, Yun Jae; Santra, Mithun; Song, Chang Wook; Jun, Yong Woong; Reo, Ye Jin; Kim, Won Jong; Ahn, Kyo Han
Abstract: Photostable and near‐infrared (NIR)‐emitting organic fluorophores with large Stokes shifts are in great demand for long‐term bioimaging at deeper depths with minimal autofluorescence and self‐quenching. Herein, a new class of benzorhodamines and their analogues that are photostable and emit in the NIR region (up to 785 nm) with large Stokes shifts (>120 nm) is reported. The synthesis involves condensation of 7‐alkylamino‐2‐naphthols with 2‐[4‐(dimethylamino)‐2‐hydroxybenzoyl]benzoic acid, which leads to bent‐shaped benzorhodamines that emit orange fluorescence (≈600 nm); however, introduction of steric hindrance near the condensation site switched the regioselectivity, to provide a linear benzorhodamine system for the first time. The linear benzorhodamine derivatives provide bright fluorescence images in cells and in tissue. A carboxy‐benzorhodamine was applied for photothermal therapy of cancer cells and xenograft cancer mice. Abstract : Brighter or darker : A new class of photostable near‐infrared (NIR)‐emitting dyes, namely linear‐shaped benzorhodamines, have been synthesized for the first time. They offer bright fluorescence images in cells and tissues. Application in the photothermal therapy of cancer cells and xenograft cancer mice was successfully conducted with a carboxy‐benzorhodamine, which shows darker emission in cells but high NIR absorption.